Impact of education on knowledge and attitude of medical students about the abuse of prescription drugs in Iran - Ghoreish, Abolfazl; Nobakht, Mahdi; Arman, Alireza; Kheradmand, Ali (Researcher Bulletin of Medical Sciences, 2018)
Introduction: The abuse of prescription drugs is considered as an important challenge for societies. Regarding many factors contributing to this challenge and its negative impact especially on young and educated people, there is an attempt in this paper to survey the impact of education on knowledge and attitude of medical students about the abuse of prescription drugs. Material and Methods: This was a quasi-experimental study, which was conducted on medical students. Two groups of 53 medical students were selected as participants for both intervention group and control group. These participants were studied using the researcher-made questionnaires about knowledge and attitude toward the abuse of prescription drugs. Results: Education plays a significant role in both raising the students’ awareness and changing their attitude about the abuse of prescription drugs. The age variable had a significant relationship with pre-training knowledge. The female participants had less pre-training knowledge about drug abuse so that it was not observed after intervention. Discussion: It is suggested that education can be considered as a strategy to prevent drug abuse and reduce the demand for drug abuse by raising the awareness and amending the attitudes as well as promoting the anti-consumption culture.